2010
DOI: 10.1371/journal.pone.0013613
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Adherence to Antiretroviral Treatment and Program Drop-Out in a High-Risk Urban Setting in Sub-Saharan Africa: A Prospective Cohort Study

Abstract: BackgroundSeventy percent of urban populations in sub-Saharan Africa live in slums. Sustaining HIV patients in these high-risk and highly mobile settings is a major future challenge. This study seeks to assess program retention and to find determinants for low adherence to antiretroviral treatment (ART) and drop-out from an established HIV/ART program in Kibera, Nairobi, one of Africa's largest informal urban settlements.Methods and FindingsA prospective open cohort study of 800 patients was performed at the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 53 publications
3
76
0
Order By: Relevance
“…Adherence to ART is crucial for treatment success among HIV patients‚ high levels of adherence is a prerequisite for maintained viral suppression and lowers risk of drug resistance, this in turn will prevent premature morbidity and mortality [1]. Low adherence is the second strongest determinant for disease deterioration and death after CD4 count.…”
Section: Background Informationmentioning
confidence: 99%
“…Adherence to ART is crucial for treatment success among HIV patients‚ high levels of adherence is a prerequisite for maintained viral suppression and lowers risk of drug resistance, this in turn will prevent premature morbidity and mortality [1]. Low adherence is the second strongest determinant for disease deterioration and death after CD4 count.…”
Section: Background Informationmentioning
confidence: 99%
“…Unfortunately, this knowledge about the disease has not resulted in appreciable changes in attitude or in behaviour modifications in the population [7,8]. For example, a study conducted in 2005 by the University of Ibadan, Ibadan, in south-western Nigeria, reported that over 90% of students possessed a good knowledge about HIV/AIDS and its transmission but that only 16.6% of sexually active students who were interviewed used condoms for protection during intercourse in the three months before the study.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial rates of decline in the number of opportunistic infections and in the prevalence of AIDS-related mortality have been observed [12,13]. A number of studies have reported reductions in the level of plasma HIV-1 RNA and increases in the number of the CD4 cell count, even among PLWHA with very low initial CD4 counts [14][15][16][17][18]. Antiretroviral drugs must be taken as a lifelong therapy and their success relies on continual adherence to the medication regimen.…”
Section: Introductionmentioning
confidence: 99%
“…The success of Option B+ depends on the retention of women in treatment programmes, which increases pressure on already strained health systems. [11,12] Recent data show that adequate adherence drops from 75.7% (95% CI: 71.5 -79.7%) during pregnancy to 53% (95% CI 32.8 -72.7) postpartum among women who meet present ART criteria. [13] The public health implications (including resistance and potential for future treatment) of reduced adherence in Options B and especially B+ are unknown and likely to be concerning.…”
Section: Economicmentioning
confidence: 99%